DETERMINAN CURAHAN JAM KERJA WANITA DI PROVINSI SUMATERA BARAT - Reni Marlina; Melti Roza Adry (Jurnal Ecogen, 2018)
This study aims to find out and analyze the influence of (1) Age on the outpouring of women's working hours in West Sumatra, (2) Education Level on the outpouring of women's working hours in West Sumatra, (3) Employment on the outpouring of women's working hours in West Sumatra, ( 4) Marriage Status towards the outpouring of working hours of women in West Sumatra, (5) Residential Area against the outpouring of working hours of women in West Sumatra, Estimation results show that (1) Age has a positive and significant effect on the Outflow of Women's Working Hours in West Sumatra, ( 2) Education Level has a positive and insignificant effect on Women Working Hours Outpouring in West Sumatra, (3) Employment has a positive and significant effect on Women Working Hours Outpouring in West Sumatra, (4) Marriage Status has a negative and insignificant effect on Working Hours Outpouring Women in West Sumatra a, (5) Territory of Residence has a negative and significant influence on Outbreaks Women's Working Hours. Taken together Age, Education Level, Marriage Status and Residential Area have a significant influence on Working Hours outfall in West Sumatera at α = 5%. Keyword: Exposure to Working Hours, Age, Education Level, Employment, Marriage Status, Residential               Area